Pengaruh Probability Ratio, Leverage Ratio, dan Market Ratio terhadap Stock Returns Mining Companies yang Listed di Indonesia Stock Exchange 2015-2020 - Silvi Nanda Setiawan; Purwohandoko Purwohandoko (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The purpose of this study was to determine how the influence of ROE, EPS, NPM, DER, and PBV on stock returns in mining companies listed on the Indonesia Stock Exchange (ISE), 2015-2020. The population taken is mining companies listed on ISE 2015-2020. This research includes quantitative research with a purposive sampling method as a determinant of the company sample, and based on the criteria, 33 companies meet the requirements. This research used secondary data sources from the official ISE website and the attached company website. Data analysis used the multiple linear regression method. The results showed that ROE and EPS did not significantly affect stock returns, while the variables NPM, DER, and PBV indicate a negative effect of these three variables on stock returns. These results suggest that the stock return decreases every time there is an increase in the NPM, DER, and PBV variables. The research results imply that investors can use the values of NPM, DER, and PBV values to analyse stock returns before investing.